Changes in irradiance and energy density in relation to different curing distances - Rafael Silva BEOLCHI; Cacio MOURA-NETTO; Renato Miotto PALO; Carlos Rocha Gomes TORRES; Bruno PELISSIER (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The present study aimed to assess the influence of curing distance on the loss of irradiance and power density of four curing light devices. The behavior in terms of power density of four different dental curing devices was analyzed (Valo, Elipar 2, Radii-Cal, and Optilux-401) using three different distances of photopolymerization (0 mm, 4 mm, and 8 mm). All devices had their power density measured using a MARC simulator. Ten measurements were made per device at each distance. The total amount of energy delivered and the required curing time to achieve 16 J/cm2 of energy was also calculated. Data were statistically analyzed with one-way analysis of variance and Tukey's tests (p < 0.05). The curing distance significantly interfered with the loss of power density for all curing light devices, with the farthest distance generating the lowest power density and consequently the longer time to achieve an energy density of 16 J/cm2 (p < 0.01). Comparison of devices showed that Valo, in extra power mode, showed the best results at all distances, followed by Valo in high power mode, Valo in standard mode, Elipar 2, Radii-Cal, and Optilux-401 halogen lamp (p < 0.01). These findings indicate that all curing lights induced a significant loss of irradiance and total energy when the light was emitted farther from the probe. The Valo device in extra power mode showed the highest power density and the shortest time to achieve an energy density of 16 J/cm2 at all curing distances.